The clinical utility of exome sequencing for risk stratification in celiac disease - Talha Asif; Michele Akalay; Wendy K. Chung; Peter H.R. Green; Xiao-Fei Kong (Journal of Human Immunity, 2026)
The potential utility of genetic testing among individuals with a positive celiac disease (CeD) family history remains limited. We performed whole-exome sequencing in a cohort of 107 cases with CeD and 117 unaffected relatives from 66 families. We assessed fourteen HLA-DQ genotypes, based on combinations of four risk haplotypes. Our cohort was predominantly of European ancestry (87%). Compared with at-risk controls, CeD cases showed a significant enrichment of high-risk (22.4 vs. 10.3%) and moderate-risk (64.4 vs. 35.9%) HLA-DQ genotypes. Stratification based on the weighted impact of fourteen HLA-DQ genotypes yields a more accurate risk assessment than assuming equal contributions from four risk haplotypes. The HLA-B*08:01 allele was more frequent in CeD patients than in controls (32.2 vs. 16.7%). Among individuals of European ancestry, the AH8.1 long haplotype was present in 62% of cases vs. 49% of controls. Whole-exome sequencing enables stratification of first-degree relatives into discrete risk categories, identifying 10% as high risk and ∼50% as having negligible genetic risk.